Surgical challenges: total laparoscopic hysterectomy of a bulky uterus weighing 4.4 kg - Venkateswaran, Nandhana; Battina, Surakshith; Battina, Sarat; Rajesweri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
With the advancements in minimally invasive surgeries, the main concern while operating huge fibroids is to avoid laparo-conversion. Performing safe and effective total laparoscopic hysterectomy for large uterus hinges largely on modifications in pre-operative preparation and modifications in surgical techniques. The procedure was done at Indigo women Centre, Chennai, Tamil Nadu, India. This procedure was performed on a 44-year-old woman with complaints of abdominal discomfort and a rapidly growing pelvic mass. Imaging suggested massive fibroid of 34 weeks size. Operative challenges included port placement, manipulation, positioning, vascularity, dissection in altered anatomy and specimen retrieval. The same was accordingly overcome by cephalad port entry, Trendelenburg and air-planning position, “two myoma screw” technique, vasopressin, appropriate energy sources use and manual morcellation. Laparoscopic approach to huge fibroids can be made feasible, provided there is sufficient preoperative preparation and surgical expertise, thereby rendering the entire benefits of minimally invasive surgery.